Reduced Wiskott-Aldrich syndrome protein expression in preeclampsia placenta impairs trophoblast syncytialization by modulating syncytin-2 via FAK/β-catenin pathway - Zhang, Shuo; Wang, Jiao; Ge, Yunpeng; Cao, Pin; Bai, Zekai; Shen, Hongfei; Wang, Dan; Qiao, Chong (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveWe investigated the role of neural Wiskott-Aldrich syndrome protein (N-WASP) in preeclampsia (PE), focusing on its regulatory impact on trophoblast syncytialization.MethodsWe analyzed placental samples from patients with PE (n = 30) and controls (n = 35) using RNA extraction, quantitative real-time polymerase chain reaction, Western blot, and immunohistochemistry. BeWo cell lines were used to model trophoblast fusion under forskolin stimulation. We explored N-WASP’s role in trophoblast cell behavior using gene knockdown and overexpression experiments. Using bioinformatics analyses and molecular docking studies, we elucidated the interaction between N-WASP and associated pathways. These findings were validated in vivo using an L-NAME PE rat model.ResultsN-WASP expression was significantly reduced in PE placentas, correlating positively with syncytin-2 and GCM1 levels. In BeWo cells, N-WASP promoted syncytialization by activating the FAK/β-catenin pathway, causing increased nuclear β-catenin translocation, glial cells missing 1 expression, and syncytin-2 transcription. Mechanistically, N-WASP interacted with myosin 1B causing FAK pathway activation. Restoring N-WASP expression ameliorated placental abnormalities and PE symptoms in vivo. We identified hydroxychloroquine as a potential N-WASP agonist, capable of enhancing trophoblast syncytialization in vitro using molecular docking. Treatment with hydroxychloroquine significantly improved clinical symptoms, including reducing elevated blood pressure, decreasing urinary protein levels, and normalizing serum creatinine concentrations in PE rat models.ConclusionWe identified N-WASP as a key regulator of trophoblast syncytialization through the FAK/β-catenin signaling pathway, influencing syncytin-2 expression. The findings reveal a novel molecular mechanism underlying PE and suggest that N-WASP is a potential therapeutic target for PE.